2014
DOI: 10.1245/s10434-014-4172-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Surgery for Colorectal Cancer in Elderly Patients: A Multicenter Matched Case–Control Study

Abstract: LAP is an acceptable alternative to OP in elderly patients with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 28 publications
5
64
4
1
Order By: Relevance
“…The proportion of elderly patients requiring major abdominal surgery is increasing (24,30). It is clear that, as patients age, there is an associated increase in comorbid conditions that often complicate the perioperative management of elderly patients who undergo major surgery (24,30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of elderly patients requiring major abdominal surgery is increasing (24,30). It is clear that, as patients age, there is an associated increase in comorbid conditions that often complicate the perioperative management of elderly patients who undergo major surgery (24,30).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that, as patients age, there is an associated increase in comorbid conditions that often complicate the perioperative management of elderly patients who undergo major surgery (24,30). MLS is currently considered to be safe and feasible in elderly patients, and evidence has suggested that it is not inferior to the open procedure, as it seems to be less physiologically stressful than conventional open laparotomy (24,30). SLS offers a potential advantage in the context of minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the noninferiority of laparoscopic D3 dissection in overall survival was not demonstrated for stage II and III colorectal cancer, because the overall survival of both arms was unexpectedly similar. Furthermore, the safety of laparoscopic surgery in elderly patients and in those with Stage IV disease for whom less invasive surgery is desirable, has been demonstrated retrospectively, and another randomized controlled trial is now underway 8,9) . Therefore, during the two decades since its initial introduction, data unique to Japan have steadily been accumulated and serves as evidence for the validity of laparoscopic surgery as a standard treatment for colon cancer.…”
Section: Colon Cancermentioning
confidence: 99%
“…Unfortunately, the non-inferiority of laparoscopic complete mesocolic excision in overall survival was not demonstrated for stage Ⅱ, Ⅲ colorectal cancer, however, because the overall survival of both arms was relatively identical and better than expected. Furthermore, the safety of LS in elderly patients and those with Stage Ⅳ disease, for whom less invasive surgery is desirable, has been demonstrated retrospectively, and another RCT is now underway [8,9] . Therefore, during the two decades since its initial introduction, data unique to Japan, serving as evidence for the validity of LS as a standard therapy for colon cancer, have steadily been accumulated.…”
Section: Colon Cancermentioning
confidence: 99%